Association of Iris Structural Measurements with Corneal Biomechanics in Myopic Eyes. (31st December 2021) - Fu, Lin; Ye, Yufeng; Jia, Xu; Zhang, Yunjie; Chen, Xiaoyu; Lian, Hengli; Yang, Weihua; Dai, Qi
Abstract : Purpose . To evaluate the relationship between iris sectional parameters on swept-source optical coherence tomography (SS-OCT) with corneal biomechanics measured by Corneal Visualization Scheimpflug Technology (Corvis ST) in young adults with myopia. Methods . 117 patients with myopia aged ≥18 years were recruited from the Eye Hospital of Wenzhou Medical University, who had complete SS-OCT and Corvis ST data. Only the left eye of each participant was selected for analysis. Iris sectional parameters included iris thickness at 750  μ m from the scleral spur (IT750), iris sectional area (I-area), and iris curvature (I-curv) measured from four quadrants. Associations between the iris parameters and corneal biomechanics were analyzed using linear regression models. Results . The mean age of the included young adults was 26.26 ± 6.62 years old with 44 males and 73 females. The iris parameters were different among the four quadrants. The nasal, temporal, and inferior quadrants of IT750, together with nasal and temporal quadrants of I-area, were correlated with corneal biomechanical parameters after being adjusted for age, gender, pupil diameter, and axial length. Thicker IT750 and larger I-area were related to a softer cornea. However, no association was found between I-curv and corneal biomechanics. Conclusions . Iris sectional parameters measured from SS-OCT images were associated with corneal biomechanical properties in myopic eyes. Thicker IT750 and larger I-area indicate a softer cornea. IT750 and I-area may provide useful information on corneal biomechanical properties in myopic eyes.